The Src homology 3 binding domain is required for lysophosphatidic acid 3 receptor-mediated cellular viability in melanoma cells. Issue 2 (28th January 2015) - Jia, Wei; Tran, Sterling K.; Ruddick, Caitlin A.; Murph, Mandi M.
Highlights: Herein we elucidate the mechanism explaining the LPA3 receptor's ability to increase viability among melanoma cells. The Src homology 3 ligand binding motif, (216)-KTNVLSP-(222), within the third intracellular loop of LPA3 mediates viability. We perform a series of site-directed mutagenesis assays to uncover this role. Abstract: The LPA3 receptor is a G protein-coupled receptor that binds extracellular lysophosphatidic acid and mediates intracellular signaling cascades. Although we previously reported that receptor inhibition using siRNA or chemical inhibition obliterates the viability of melanoma cells, the mechanism was unclear. Herein we hypothesized that amino acids comprising the Src homology 3 (SH3) ligand binding motif, R/K-X-X-V/P-X-X-P or (216)-KTNVLSP-(222), within the third intracellular loop of LPA3 were critical in mediating this outcome. Therefore, we performed site-directed mutagenesis of the lysine, valine and proline, replacing these amino acids with alanines, and evaluated the changes in viability, proliferation, ERK1/2 signaling and calcium in response to lysophosphatidic acid. Our results show that enforced LPA3 expression in SK-MEL-2 cells enhanced their resiliency by allowing these cells to oppose any loss of viability during growth in serum-free medium for up to 96 h, in contrast to parental SK-MEL-2 cells, which show a significant decline in viability. Similarly, site-directed alanine substitutions of valine and proline, V219A/P222A or 2aa-SK-MEL-2 cells, did not significantly alter viability, but adding a further alanine to replace the lysine, K216A/V219A/P222A or 3aa-SK-MEL-2 cells, obliterated this function. In addition, an inhibitor of the LPA3 receptor had no impact on the parental SK-MEL-2, 2aa-SK-MEL-2 or 3aa-SK-MEL-2 cells, but significantly reduced viability among wt-LPA3-SK-MEL-2 cells. Taken together, the data suggest that the SH3 ligand binding domain of LPA3 is required to mediate viability in melanoma cells.